INOVASI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN (STUDI KASUS PONPES AL – IRSYAD AL – ISLAMIYAH GENTANG LOMBOK TENGAH) - Junaidi (UNISAN JURNAL, 2024)
Good strategic planning will improve the quality of good educators as well. However, good planning is sometimes not matched by good execution. Therefore the researchers took the title "Implementation of Strategic Planning in Improving the Quality of Educators at Integrated Ponpes Al – Irsyad Al – Islamiyah Gentang Lombok Tengah, Regency". This research took place at Ponpes Al – Irsyad Al – Islamiyah Gentang Lombok Tengah, Regency. The formulation of the problem in this research is "How is the implementation of a strategic role in improving the quality of teaching staff at Ponpes Al – Irsyad Al – Islamiyah Gentang Lombok Tengah, Regency?". Data collection techniques in this study include: observation, interviews, and documentation. Data analysis namely data reduction, data presentation, and data verification or drawing conclusions.Then tested the validity of the data with the source triangulation technique and research techniques. The conclusion from the results of this study is that the implementation of the strategic plan at the One Roof Ponpes Al – Irsyad Al – Islamiyah Gentang Lombok Tengah, Regency has been good, including the implementation of the strategic plan at the One-Stop Integrated Ponpes Al – Irsyad Al – Islamiyah Gentang Lombok Tengah, Regency. steps namely strategic planning planning, strategic planning implementation, and strategic planning evaluation